Quality of Work-Life and Employee Job Satisfaction in Nepalese Organizations - Paudel, Manoj (Journal of Nepalese Management and Research, 2023)
The purpose of this study is to explore and examine the factors of quality of work life in different organizations in the context of Nepal. In this study, causal comparative research design is used to determine the causes and consequences of selected variables. Information is gathered from 422 staff working in different organizations in different sectors of work and job positions using a set of structured questionnaires. For the analyses, mean, standard deviation, f-test, and multiple regression are used. The study revealed that career development and growth, empowerment and teamwork are found to be statistically significant